Produção de mudas de cajarana submetidas a níveis de efluente doméstico tratado e manejos de aib - Queiroz, Jorge Luis Fabricio de (Universidade Federal Rural do Semi-Árido, 2017)
The objective of this study was to evaluate the production of cassava seedlings (Spondias spp) by the cutting method under the effect of irrigation with treated domestic effluent associated with different doses of AIB. The experiment was carried out in a greenhouse with 50% shading in the Department of Environmental Sciences and Technology of UFERSA in Mossoró (RN) from November 2016 to March 2017. The cuttings were collected from a single adult mother plant, in great vigor, at the end of the vegetative rest, where it was defoliated, with swollen buds, with no evidence of pest attack or disease. The experiment was carried out in a completely randomized design in a 4 x 4 factorial scheme consisting of four doses of treated domestic effluent (EDT) diluted in supply water (E1 = 0% of EDT + 100% AA (control), E2 = 33.3% of EDT + 66.7% of AA, E3 = 66.7% of EDT + 33.3% of AA and E4 = 100% of EDT + 0% AA) to be used in irrigation and four managements of AIB diluted in water at 6,000 ppm, M3 = AIB diluted in Alcohol at 4,000 ppm and M4 = AIB diluted in Talc at 5,000 ppm), with four replicates, 64 experimental units. Each experimental unit contained 6 useful cuttings, where the number of shoots, length of shoots, diameter of shoots, number of leaves, leaflets, roots, length and volume of roots were evaluated; dry mass of shoot, root and total, percentage of cuttings sprouted, calloused, rooted and sprouted with root. It was verified that, at 115 days after cutting, treated domestic effluent is feasible for irrigation of cassava seedlings in its diluted or concentrated form, presenting as an alternative water source for irrigation and the use of IBA at a concentration of 5,000 ppm diluted in Talc is satisfactory for the propagation of cassava seedlings by means of semi-herbaceous cuttings, besides being easier to handle compared to the use of liquid dilutions
Keywords: Efluente doméstico tratado; AIB; Spondias spp; Manejo de solo e água; Treated domestic effluent; AIB; Spondias spp; Soil and water management; CIENCIAS AGRARIAS::AGRONOMIA::CIENCIA DO SOLO::MANEJO E CONSERVACAO DO SOLO